Percepções e práticas de lazer dos servidores técnico-administrativos em educação da Universidade Federal de Minas Gerais - Eliane Leroy Alves (2023)
The objective of this research was to understand the leisure practices experienced by the technical-administrative staff, both within and outside UFMG, and to investigate their perception regarding the leisure actions and activities proposed by the Federal University of Minas Gerais, as well as their actual participation. The adopted methodology was a descriptive-quantitative study, preceded by documentary research as the primary source of data, which revealed information about the subjects and the institution, both of which were objects of analysis in the research. Data were collected through the administration of an electronic questionnaire to all active technical-administrative staff members at the Pampulha Campus and Health Campus, Faculty of Law and School of Architecture , who had a registered email address with the institution. The results indicated that a significant number of staff members reported having leisure activities in their routines, including watching movies and series, going to the cinema, spending time with family and friends, attending concerts, engaging in physical activities, and traveling. Inhibiting factors for leisure practices were perceived as a lack of time, money, and excessive workload. The respondents primarily perceive leisure as entertainment, improving the quality of life, free time, relaxation, and a break from their routine. They believe that leisure practices contribute to stress reduction, improved physical and mental health, as well as overall quality of life and social well-being. Those who visit the University Sports Center typically do so for sports, reading, and using the pool. However, the space is used more frequently only during scheduled events. This is mainly due to issues related to the infrastructure of the Sports Center, lack of time, distance from home, busy daily schedules, and fatigue from daily activities. Regarding the Quality of Life at Work Program (PRORH/UFMG), it was found that there is a reduced number of active participants, many who have participated in the past but do not currently, and a significant number of people who have never participated. Although they recognize that the activities offered by the program are considered leisure, among the main limitations for participation are a lack of time, difficulty in balancing them with domestic and family obligations, the timing of the activities, selection criteria, and limited available slots. Therefore, it was concluded that, although the university has spaces and initiatives related to sports and leisure, the limitations mentioned above have hindered or made it difficult for staff members to participate effectively. Currently, these actions fall short of their intended purpose, and if reevaluated, they could become more effective. If the university can recognize leisure as a tool capable of improving work relationships and if staff members can perceive the existence of dedicated leisure time offered by the university, work relationships could change.